The adsorption of benzene mono- and multilayers on Ni(111) studied by TPD and LEED - Steinrück, Hans-Peter; Huber, W.; Pache, T.; Menzel, Dietrich (Surface Science, 1989)
Benzene adsorption on Ni(111) has been studied by LEED and TPD for adsorption temperatures between 110 and 310 K. At initial coverages θ < 0.05 ML (relative to Ni) complete decomposition of benzene occurs upon heating above 650 K. At higher coverages (θ > 0.05 ML) molecular desorption precedes decomposition. The saturation coverage of chemisorbed benzene can only be achieved at adsorption temperatures below 270 K and reveals a sharp (√7×√7)R19.1° LEED pattern corresponding to a coverage of 0.143 ML. This LEED pattern disappears upon heating to 300 K; simultaneously a very sharp molecular benzene desorption peak is observed at 294 K, indicating that desorption is coupled to this order-disorder phase transition. A previously reported (2√3× 2√3)R30 ° structure for room temperature adsorption can only be observed by coadsorbing CO; the relative coverages in the coadsorbed benzene + CO layer are θ : theta; = 1:2. Adsorption of benzene at 110 K leads to the formation of multilayers. Three distinct states, α , α and α can be resolved with desorption temperatures of 154, 136 and 146 K, respectively. The α peak corresponds to the first physisorbed layer on top of the chemisorbed benzene, probably also oriented parallel to the surface. The α peak exhibits typical zero-order desorption behaviour and is attributed to bulk sublimation. The α peak seems to be due to a transition layer between the α layer and bulk benzene. This behaviour is similar to that observed before on Ru(001). For chemisorbed and physisorbed benzene we compile and compare the results on other surfaces. © 1989.